Bone density in patients with late onset Pompe disease. - Papadimas, George; Terzis, Gerassimos; Papadopoulos, Constantinos; Areovimata, Anna; Spengos, Konstantinos; Kavouras, Stavros; Manta, Panagiota (Int J Endocrinol Metab, 2012)
BACKGROUND: Pompe disease is an inherited metabolic disorder characterized by α-glycosidase deficiency, which leads to lysosomal glycogen accumulation in many different tissues. The infantile form is the most severe with a rapidly fatal outcome, while the late onset form has a greater phenotypic variability, characterized by skeletal muscle dysfunction and early respiratory involvement. Bone mineral density (BMD) has been recently reported to be reduced in many patients with both forms of the disease. Enzyme replacement therapy (ERT) is now available with an undefined, impact on BMD in patients with late onset disease. OBJECTIVES: The present study aimed to investigate BMD in patients with late onset form of Pompe disease before and after ERT initiation. PATIENTS AND METHODS: Dual x-ray absorptiometry (DEXA) was examined in four newly diagnosed patients with late onset Pompe disease and in four adults under ERT before and after ERT initiation with a treatment duration of 18 to 36 months. RESULTS: The initial DEXA showed normal total body BMD z-score in all the patients, while L2-L4 and femoral neck BMD was reduced in three and two patients, respectively. After ERT administration, two patients had an improvement in L2-L4 lumbar spine and one patient in femoral neck BMD z-score with values within normal range. CONCLUSIONS: The results suggested that regional BMD may moderately reduce in some patients with the late onset form of Pompe disease, although profound osteopenia was not observed. The improvement of measurements in L2-L4 and femoral neck BMD z-score in some patients with low pre-treatment values after ERT administration needs to be confirmed in larger scale studies.